Efficacy of Argon Plasma Coagulation Treatment in Radiation Colitis Patients and Its Confounding Factors - Ariadno, Aru; Makmun, Dadang; Sulaiman, Andri S; Koesnoe, Sukamto (Jurnal Penyakit Dalam Indonesia, 2020)
Introduction. Argon plasma coagulation (APC) is widely used in the treatment of radiation colitis among patients with gynecology, colorectal and urology malignancy. This study aimed to measure the result of APC conducted on radiation colitis patients and its counfounding factors. Methods. An analytic descriptive study with retrospective cohort design was conducted among radiation colitis patients received APC treatment in Cipto Mangunkusumo Hospital, Jakarta. Data were collected from medical record database between April 2012 until October 2019. Results. As much as 180 radiation colitis patients received APC treatment fulfilled inclusion criteria with characteristics female patients (89.4%) and age >50 years old (83.9%) were included in this study. Types of tumor were dominated by gynecology malignancy (88.9%). As much as 81.3% subjects had successful APC treatment. Median number of efficacy of APC treatment in this study was 2 sessions. All of the subjects had anemia before the first APC treatment. There was improvement in Hb level, median Hb before the first APC treatment was 8 g/dL (3-11 g/dL) and median Hb level before the last APC treatment was 12 g/dL (10-14 g/dL). As much as 59.2% subjects who had successful APC treatment were no longer had anemia after APC treatment, improvement of anemia status was 1.628 times more likely in subjects who had successful APC treatment compared to subjects who did not have successful APC treatment (p=0.017). Age, gender, malignancy types, hypertension, and diabetes mellitus were not the confounding factors to anemia status in successful APC treatment. Conclusion. There was improvement in anemia status on radiation colitis patients receiving APC treatment in RSUPN-CM.